PERSEPSI GURU TENTANGPELAKSANAAN SUPERVISI OLEH KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN PADANG PANJANG BARAT KOTA PADANG PANJANG - Marini Putri (Universitas Negeri Padang, 2014)
The goal of this research are to see information about perception of teachers on the implementation of supervision . The population is 203 teachers and the sample is 65 people that taken by Stratified Proportional Random Sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score . The result of this research are the perception of teachers on the implementation of supervision by the headmaster at high school Negeri Kecamatan Padang Panjang Barat Kota Padang Panjangstay in quite accomplished category. Key word : Perception of teachers on the implementation of supervision.